The Relationship between Sustainability Reporting, Corporate Governance, and Firm Value: The Mediating Role of Financial Performance in Food and Beverage Companies Listed on the Indonesia Stock Exchange - Nisa Fitriyani; Agus Sihono (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Purpose: This study examines the effect of sustainability reporting and corporate governance on firm value with financial performance as the mediator. Methods: The research sample consists of 99 data from 33 Food and Beverage companies listed on the Indonesian Stock Exchange (IDX) between 2022 and 2024. This study adopted a quantitative approach using secondary data from financial reports. Purposive sampling technique was used with Smart-PLS4 as the research statistical testing tool. Results: The test results show that sustainability reports (SR) have a positive and significant effect on firm value (Tobins’Q), but do not significantly affect financial performance (ROA). Board meetings (BM), as a proxy for corporate governance, also have a positive and significant effect on firm value (Tobins’Q), but a negative and significant effect on financial performance (ROA). Financial performance (ROA) has a positive and significant effect on firm value (Tobins’Q) and is proven to significantly mediate the relationship between board meetings (BM) and firm value (Tobins’Q) in a negative direction, but does not significantly mediate the relationship between sustainability reports (SR) and firm value (Tobins’Q). Implications: For companies, sustainability reports should be viewed as a transparent, long-term investment focused on tangible performance, supported by optimized board meetings and corporate governance. For investors, information on sustainability, governance, and financial performance is crucial for decision-making, while for regulators such as the Financial Services Authority (OJK), these findings serve as a basis for strengthening regulation, transparency, and market confidence.